Penggunaan Jargon di Kalangan Waria Kota Bitung - Wakari, Rosytha B. (Kajian Linguistik, 2017)
The study of the jargon used to describe transvestites Bitung do the language used by the transvestites in interacting orally. This study shows that the jargon that live among transvestites Bitung derived from a variety of languages, namely Indonesian (shepherds' fat ', the mill crazy, a tangle of love' selling themselves' royal 'work', golden 'piss', the field' hungry 'rose' like '). English (drinken 'drink', eaten 'eat', homre 'home', sleepen 'sleep'). Germany (kleine 'small' and spielen, 'play'). Dutch (betalen 'buy / pay' geld 'money', groot 'big', stil 'silent'). Regional language Sangihe and Java (enjeh 'yes' and nar 'go walking'. Therefore, it is not uncommon to communicate everyday, transvestites often change (switching) languages, from one to the other language. Therefore uniqueness and kevariasian language, researchers interested in conducting research on the use of jargon among transvestites particularly Bitung City. this study aims to (1) identify, classify, and analyze the jargon used by transvestites Bitung, (2) analyze the functions of jargon which use among transvestites Bitung.Descriptive qualitative study was conducted in three phases, namely the phase of the provision of data, data analysis stage, and the stage presentation of the results of the data analysis. The data used as material analysis in this study is a narrative of data studied for 5 months (August-December 2016) derived from IWABI ranging from chairman to members totaling 10 participants transvestites. those aged between 18 and 33 years old. Through this technique, note and record using the phone / video, as much as 2 or 3 times for each informant. Each speech they present, then selected and categorized based on the needs of researchers to solve existing problems, the form, meaning and function of jargon transvestites Bitung City.Keywords: Jargon, transvestites, Bitung.